The Role of Environmental and Behavioral Uncertainty as a Mediator of Situation-Performance Relationships - Weed, Stanley E.; Mitchell, Terence R. (Academy of Management Journal, 1980)
The causes and consequences of two types of uncertainty (environmental and behavioral) were investigated in a simulated job environment. Employees worked with a structuring or considerate leader, on a structured or unstructured task, and with or without a goal. The structuring leader and structured task produced greater certainty than the considerate leader or the unstructured task. Goal setting had no effect. The same independent variables and increased certainty resulted in higher performance.